Teaching database concepts to video game design and development students (Revista Lusófona de Educação, 2018)
A video game design and development degree is a very specific choice for students, who are mainly interested in making games or taking part in the game development process. Databases are not an apparent requirement in order to pursue these goals, often leading to a lack of motivation and interest in the subject. Nonetheless, a number of Bachelor degrees in video game design and development acknowledge the importance of Databases, and offer it as a mandatory course in their curricula. However, the subject exposition is often done in the context of typical database areas of application, such as business settings, websites or library and university management. In this paper we describe and propose four classroom database problems specifically designed for video game design and development students. It is our belief that using a context-aware approach yields not only more motivated students, but students with a better understanding of database concepts so often necessary to design and develop computer games.Keywords: programming curriculum; video game development; databases; SQL